2005
DOI: 10.1016/j.chb.2004.02.014
|View full text |Cite
|
Sign up to set email alerts
|

The use of microworlds to study dynamic decision making

Abstract: Dynamic decision-making (DDM) research grew out of a perceived need for understanding how people control dynamic, complex, real-world systems. DDM has describable characteristics and, with some unavoidable sacrifice of realism, is suitable for study in a laboratory setting through the use of complex computer simulations commonly called 'microworlds'. This paper presents a taxonomic definition of DDM, an updated review of existing microworlds and their characteristics, and a set of cognitive demands imposed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
149
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 189 publications
(154 citation statements)
references
References 22 publications
(26 reference statements)
0
149
0
2
Order By: Relevance
“…Because DDM tasks have very specific abstract characteristics that are generalizable across many domains (Gonzalez, Vanyukov, & Martin, 2005), it is expected that results from this study could be reproduced with other DDM tasks; again, however, more empirical support is needed here.…”
Section: Limitationsmentioning
confidence: 87%
“…Because DDM tasks have very specific abstract characteristics that are generalizable across many domains (Gonzalez, Vanyukov, & Martin, 2005), it is expected that results from this study could be reproduced with other DDM tasks; again, however, more empirical support is needed here.…”
Section: Limitationsmentioning
confidence: 87%
“…This enables problem solvers to match their prior knowledge with the structural and procedural properties of the transfer problem, and, by assessing the similarity, they can bring relevant knowledge to bear on the task. Where dissociations are found (Berry & Broadbent, 1988;Dienes & Fahey, 1995, 1998, problem solvers learn without the benefit of hypothesis testing (e.g., Geddes & Stevenson, 1997;Gonzales, Vanyukov, & Martin, 2005;Sweller, 1988;Vollmeyer et al, 1996), and in some cases, through explicit instruction, are actively discouraged from doing so (e.g., Berry, 1991). Along with preventing associations between declarative and procedural knowledge, constraining hypothesis testing also appears to limit the extent to which control behaviors transfer.…”
Section: Successful Transfer Of Complex Control Behaviorsmentioning
confidence: 99%
“…WPP embodies the integral characteristics of all DDM tasks (Brehmer & Dörner, 1993;Gonzalez et al, 2005). First, WPP is a dynamic resource allocation task.…”
Section: Water Puriwcation Plant: a Ddm Taskmentioning
confidence: 99%
“…Research indicates that feedback interventions may beneWt individuals' performance of simple tasks but not of complex tasks, of tasks that demand low rather than high cognitive ability, and of well-practiced tasks but not novel ones (Kluger & DeNisi, 1996). These are discouraging results for researchers studying DDM support, because most DDM tasks are complex, demand high cognitive ability even after extensive task practice, and present decision makers with constantly changing and novel stimuli (Ackerman, 1992;Brehmer & Dörner, 1993;Gonzalez, Vanyukov, & Martin, 2005;Lerch & Harter, 2001) The study reported here examined forms of decision support that appear to address the real-time constraints of DDM and the learning-process demands of DDM. It has been argued that achieving an improved understanding of individuals' learning processes will enable researchers to better understand performance in DDM tasks (and, subsequently, to design eVective forms of decision support) (Gibson, Fichman, & Plaut, 1997;Gonzalez, Lerch, & Lebiere, 2003).…”
Section: Introductionmentioning
confidence: 99%